MEDICAL AND LEGAL PERSPECTIVES OF THE AIR CONVENTIONS’ ‘BODILY INJURY’ - Naboush, Dr. Eman (Academy of Social Science Journal, 2017)
The term ‘bodily injury’ is being used by the carriage by air conventions and some national laws in the United Kingdom. This term does not seem to be legally familiar in the English legal system. The main issue of this paper is to determine the scope of this term and whether it covers the mental conditions and illness or not. Both the medical and legal perspectives of this term were analysed to determine which perspective is adopted by the courts. According to the medical dictionaries and the World Health Organisation’s (WHO) classification of diseases, the word ‘bodily’ is not a medical term and the word ‘injury’ refers to a specific group of external causes of illnesses which cannot be taken to be the intended meaning in the carriage by air conventions. Notably, mental disorder is classified as one of the twenty-two categories in the International Classification of Diseases and Related Health Problems. ‘Bodily injury’ as a legal term was analysed under the English and French laws with caution, because a term used in an international convention is not intended to be given a meaning according to a particular legal system. The phrase ‘bodily injury’ is does not convey a technical legal meaning. The term ‘actual bodily harm’, which was used in a criminal act in the UK, includes both psychiatric injuries as well as physical ones. However, instead of the term ‘bodily injury’, English tort law used ‘personal injury’ referring to both physical and psychiatric injuries. The term ‘bodily injury’ is used in insurance contract, and the courts ruled in favour of extending it to cover both physical and psychiatric injuries. Finally, it is noteworthy that mental illness or injury should be distinguished from pain or suffering which are mere feelings and therefore not compensable in general.